The Role of the Head of the Education Service Technical Implementation Unit (UPTD) in Improving Employee Performance in Sangir Batang Hari District, South Solok Regency - Yatra, Belli; Meilina, Susiyanti (Adabi : Journal of Public Administration and Business, 2023)
This study aims to find out and examine how the role of the Head of the Sangir Batang Hari Education UPTD is whether it has been carried out properly or not. This study uses a descriptive qualitative method which explains in depth the role of the Head of Education UPTD Sangir Batang Hari District, South Solok Regency in improving employee performance. Data collection techniques using interview techniques, observation and documentation. Data analysis techniques, namely by triagulation, data reduction, data presentation and drawing conclusions. The result of this research is that the role of the Head of the Sangir Batang Hari Education UPTD has been very good in carrying out his role in improving employee performance and discipline. Meanwhile, the obstacle faced by the Head of the Education UPTD Sangir Batang Hari Subdistrict in improving employee performance at the Education UPTD itself, namely the most important obstacle was the lack of staff in the Education UPTD which was one of the most influential obstacles in improving performance at the Education UPTD. Furthermore, the constraints that exist in the UPTD itself also affect the human resources (HR) in the UPTD of Education who are not yet disciplined. Factors that influence the performance of UPTD Education staff in Sangir Batang Hari District, namely: Head of UPTD Education in Sangir Batang Hari District, South Solok Regency in order to increase the role that is more motivating for employees to carry out tasks according to the goals to be achieved so that employee performance can be even better for the sake of structure work and goal attainment.